Core-shell structured nAl@F-x nanocomposite: preparation and their improved combustion performances. Issue 1 (2nd January 2022) - Hao, Dongyu; Hu, Yinghui; Wang, Fang; Xia, Debin; Wang, Dakang; Fan, Ruiqing; Yang, Yulin; Lin, Kaifeng
ABSTRACT: In this work, a novel Al2 O3 -free core-shell structured nAl@aluminum-perfluorooctanoate (F-x) nanocomposite has been prepared via a self-assembly approach. The Al2 O3 shell was first removed by hydrofluoric acid (HF) solution, and then the perfluorooctanoic acid (PFOA) was coated on the surface of nAl by a self-assemble reaction. The thickness of the obtained F-x layer can be easily tuned by using different amount of PFOA based on the chemical interaction between nAl and PFOA molecules. The obtained nAl@F-x nanocomposite showed an enhanced exothermic and combustion performance due to the synergetic effect between F-x and nAl and the mesoporous structure in situ formed during the combustion process. This work demonstrated that nAl@F-x nanocomposite prepared by PFOA coating on nAl could effectively solve the detrimental effect of in situ formed Al2 O3, thus enhancing the combustion and thermal reaction performances, which showed great potential to be applied in solid rocket propellant. GRAPHICAL ABSTRACT: uf0001